Loss-of-function mutations in the CABLES1 gene are a novel cause of Cushing's disease. Issue 8 (August 2017) - Hernández-Ramírez, Laura C; Gam, Ryhem; Valdés, Nuria; Lodish, Maya B; Pankratz, Nathan; Balsalobre, Aurelio; Gauthier, Yves; Faucz, Fabio R; Trivellin, Giampaolo; Chittiboina, Prashant; Lane, John; Kay, Denise M; et al.
Abstract : The CABLES1 cell cycle regulator participates in the adrenal–pituitary negative feedback, and its expression is reduced in corticotropinomas, pituitary tumors with a largely unexplained genetic basis. We investigated the presence of CABLES1 mutations/copy number variations (CNVs) and their associated clinical, histopathological and molecular features in patients with Cushing's disease (CD). Samples from 146 pediatric (118 germline DNA only/28 germline and tumor DNA) and 35 adult (tumor DNA) CD patients were screened for CABLES1 mutations. CNVs were assessed in 116 pediatric CD patients (87 germline DNA only/29 germline and tumor DNA). Four potentially pathogenic missense variants in CABLES1 were identified, two in young adults (c.532G > A, p.E178K and c.718C > T, p.L240F) and two in children (c.935G > A, p.G312D and c.1388A > G, and p.D463G) with CD; no CNVs were found. The four variants affected residues within or close to the predicted cyclin-dependent kinase-3 (CDK3)-binding region of the CABLES1 protein and impaired its ability to block cell growth in a mouse corticotropinoma cell line (AtT20/D16v-F2). The four patients had macroadenomas. We provide evidence for a role of CABLES1 as a novel pituitary tumor-predisposing gene. Its function might link two of the main molecular mechanisms altered in corticotropinomas: the cyclin-dependent kinase/cyclin group of cell cycle regulators and the epidermal growth factor receptor signaling pathway. Further studies are needed to assess the prevalence of CABLES1 mutations among patients with other types of pituitary adenomas and to elucidate the pituitary-specific functions of this gene.